An Analysis of Representation of Gossip in Lauren Weisberger’s Everyone Worth Knowing - Ramadani Saputra (Universitas Pendidikan Indonesia (UPI), 2016)
Gossip has been famously regarded as one form of communication. People interact with each other and end up in gossiping about other people. The issue of gossip is still considered as trivial thing and the word gossip itself is still labeled with negative value. This research entitled “An Analysis of Representation of Gossip in Lauren Weisberger‟s Everyone Worth Knowing” attempts to reveal the benefits of gossip which becomes the main issue of the novel. Using James O. Young’s representation theory and theory of gossip by Elaine Lui, this research provides another perspective of gossip by portraying the function and power of gossip, and also how gossip works in the society. The findings show that the issue of gossip is closely related to famous people like celebrity, and gossip has also been used as a commodity to reach certain purposes.Keywords: gossip, representation, celebrity